Geodynamics and Ore Content of Proterozoic Maphites in the Central Part of the Aldan-Stanovoy Shield (Southern North Asian Craton) - A. A. Kravchenko; A. V. Okrugin; V. I. Beryozkin; N. V. Popov; E. E. Loskutov (Геодинамика и тектонофизика)
The study of diverse mantle-derived igneous complexes is important for interpreting geodynamic events, ore deposits formation mechanisms, and ore-forming fluid sources. Modern studies of orogenic gold deposits in the Precambrian metamorphosed terranes emphasize the importance of subduction-enriched lithospheric mantle in the ore formation processes. Orogenic gold mineralization in the Nimnyr terrane of the Aldan-Stanovoy shield is confined to the outcrops of mafic granulites from the Medvedev complex, intruded and metamorphosed 1.92–1.90 Ga ago at the final stage of the collision process. The Medvedev complex and ore bodies are intersected by non-metamorphosed dolerites of the 1.87 Ga Timpton-Gynym and 1.75 Ga Timpton-Algamai dike belts formed under conditions of post-collisional and intracontinental extension. The mantle-derived igneous complexes, presenting in a variety of geodynamic settings and ore mineral formation stages, make it possible to identify compositional and evolutionary features of the mantle in connection with ore formation processes. To do this, there were determined rock-forming oxide and trace element concentrations in pre-ore mafic granulites of the Medvedev complex and post-ore dolerites. Based on the geochemical data, there was a reconstruction of rock and mantle source type formation conditions. It was found that the rocks of the Medvedev complex are plume-derived. Doleritic melt formation was contributed to by the subduction-enriched lithospheric mantle material. There is a possility of different degrees of source melting and interaction of plume with the enriched lithospheric mantle at the final stage of the collision process. The obtained results can be used to refine the geodynamic models of gold mineralization formation in the central part of the Aldan-Stanovoy shield. There has been proposed one of the standard models.